CFD Simulation With Ansys Effect Of Twisted Tape Ratio On Nusselt Number and Reynold Number Solar Collector - okba, singgah khairun; Ridwan, Ridwan; Setyawan, Iwan (Eksergi, 2022)
Solar collector is one of the tools used to harness solar power and then convert it into heat which is used to heat water. The solar collector used is a flat plate type solar collector, the drawback of this solar collector is its low efficiency value. One method that can be used to increase its efficiency is to add twisted tape. Twisted tape serves to increase the value of the nusselt number and reynold number, where the increasing nusselt number and reynold number means the efficiency will increase, the Twisted Tape Ratio is the ratio between the distance of two peaks (H) and the width of the pipe (D). In this study using three variations of the tape ratio, namely 5,4, and 3, at Y = 5 the highest nusselt value and the Reynold number 4000 and Nuselt Number 24 were used, this is because the Twisted Tape ratio is 4 and 3 forms of twisted tape inhibit the flow. which causes a decrease in the value of the nusselt number and reynold number.